Agro Base Styrofoam / Muhammad Ibnu Hafiz Mohamad Padzil ... [et al.] - Mohamad Padzil, Muhammad Ibnu Hafiz; Shamsudin, Hazira; Ducth, Albayinah; Majawab, Corrney D.V; Nurman, Nurmawati (2009)
Agro Base Styrofoam established in year 2010 following the initiative to venture into the business of ecological conservation, an industry that is increasingly crucial to developed as well as developing nations but often neglected by business communities. Being the first company in Borneo to produce packaging products made of natural 'Oil Palm Fiber', Ecological Packaging has successfully developed a wide range of ecofriendly products that promises to revolutionize the packaging industry. Driven by a team of technically skilled and experienced Research & Development (R&D) personnel with the latest state-of-the-art manufacturing facility located in KKiP, Kota Kinabalu Sabah, an ecologically advanced technology been developed, responsible for the conversion of palm biomass industries into ecological raw materials used to produce eco-friendly packaging products. Our company produces Styrofoam from natural oil palm fiber, that are the product is totally safe environment and good for people. We produce the Styrofoam that size per piece is 60x175x135(mm). This product contains various key values that surpass the limitations of conventional packaging products, making it a revolutionary product that is Bio-degradable and convertible into natural fertilizers, suitable for food packaging and microwaveable and also it able to preserve freshness for a long period of time.Target market is a group of customers, who can be identified to have certain needs and wants that can be satisfied by the business through the supply of goods and services. The existence of a target market does not mean that a business should ignore the other groups of customers that exist in the same market. These groups may be secondary market and may bring income to the business through segmentation a business can identify an overlooked market and develop a product to exploit that market. Our business marketing is not too big. However, we have decided to focus our business marketing in Kota Kinabalu and other potential place in Sabah firstly for the purpose to consolidate our business before develop it in other place like Sarawak and peninsular of Malaysia, we fully confident if one day we can supply this product to the other country.